Attitudes of Czech pupils who are deaf or hard of hearing towards physical education classes: A comparison of gender differences - Petra Kurková (Palacký University Olomouc, 2018)
Background: Physical education is an organised form of physical activity and can be viewed as an interaction between the ideas of difficulty and importance that are gradually developed by both the teacher and the pupil. Objective: The objective of this study was to analyse differences in pupils' attitudes by gender in the second stage of primary schools for the deaf or hard of hearing in physical education classes. Methods: Participants were 86 pupils who are deaf or hard of hearing (boys, n = 56; 65.1%; girls, n = 30; 34.9%). The mean age and standard deviation was 14.3 ± 1.4 years. The data were described using absolute and relative frequencies, including the mean and standard deviation. The non-parametric Mann-Whitney U-test was used to assess differences between two independent groups (boys versus girls). For calculation of effect size coefficient abs(r) was used. All tests were performed at a level of α = .05. Results: In physical education classes, statistically significant differences were found in the effort made, with boys making more effort in physical education classes than girls (Z = -2.048; p = .041; abs(r) = .221). For the other indicators under review, no differences were found. Conclusion: Both boys and girls consider physical education to be their favourite subject, it makes them feel good, and there are no major differences in their emotional response. However, boys make much more effort in physical education classes.